Análise do efeito distributivo da precificaç\~ao de carbono no Brasil - Amaro Olimpio Pereira Júnior; Rodrigo Maia; Mário Jorge Mendonça; Paulo Roberto Santos Casaca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study aims to analyze the distributional effects of carbon pricing in Brazil. The subject has gained importance with initiatives such as the PMR Brazil Project and RenovaBio, but discussions have been limited to the possible loss of competitiveness of national products. Thus, scenarios built from a computable general equilibrium model were analyzed to assess the impacts of different forms of taxation. The results showed that mechanisms considering taxes without distinction between more or less emitter sectors have little impact on income distribution. In any case, compensation measures are needed to further mitigate the effects on the lower income classes.
Keywords: C67; D57; C80; 330; income distribution; computable general equilibrium models; carbon pricing